Analisis Pelaksanaan Mutasi Aparatur Sipil Negara Eselon III Dan IV Lingkup Pemerintah Kabupaten Buton Utara - La Ode Sajali; Jopang Jopang; Yaya Mulyana (UIR Press, 2022)
This study aims to analyze the implementation of echelon III and IV ASN mutations in the North Buton Regency Government. This study uses a qualitative approach, with an analysis focus on the implementation of echelon III and IV ASN mutations. There were 9 informants in this research, namely the Regional Secretary, Head of BKPSDM, Head of Mutation Division, 3 echelon III officials and 3 echelon IV officials. The selected informants were determined purposively. Data were collected through observation, interviews, and document studies. The data obtained were then analyzed interactively with an analytical model referring to Milles and Huberman (1992), covering data collection, data presentation, data reduction and drawing conclusions. The results showed that the implementation of the transfer of echelon III and IV employees within the scope of the North Buton Regency Government was still dominated by the spoil system. The mutations carried out are based on the principle of kinship and on the basis of likes and dislikes. These likes and dislikes are closely related to the behavior of employees who make political contributions to the implementation of democratic momentum in North Buton Regency. However, mutations based on considerations of the merid system and spoiled system are still the main considerations in the implementation of echelon III and IV ASN mutations in North Buton Regency.